Development and Evaluation of Aloe vera Enriched Flavored Whey Beverage - Kumar, S. Sharath; Swathi, S.; Swarnalatha, G.; Kartikeyan, S. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted from July, 2024 to Dec, 2024, at the College of Dairy Science and Food Technology, Dau Shri Vasudev Chandrakar Kamdhenu Vishwavidyalaya, Raipur, Chhattisgarh, India. Coupling whey and herbs would yield a refreshing nutrient rich drink with improved therapeutic properties. In the present investigation, paneer whey has been used as a base material to prepare flavoured whey beverage by incorporating Aloe vera juice and to evaluate their physical, chemical and sensory properties. Different concentrations 0, 5, 10, 15 and 20% of Aloe vera juice were optimized to prepare whey beverage. The effect of Aloe vera juice incorporation on sensory and physico-chemical characteristics of control and fortified whey samples were studied. The treatment samples were observed significant different and comparable to control samples on “9 point Hedonic sensory evaluation score card. The physico-chemical analysis of stored beverage samples i.e. viscosity, TCH, ash decreased and acidity increased. During the storage period the sensory scores beverage samples i.e. colour and appearance (C&A) score, flavour score, taste score, consistency score and Overall acceptability (OA) score decreased from 7.40 to 7.15, 7.42 to 6.10, 7.35 to 6.10, 7.37 to 6.30 and 7.27 to 6.25 on 9 point hedonic scale respectively.The performance of 10% and 15% Aloe vera juice incorporated whey based beverages was better than control in terms of sensory quality during the storage temperatures. However the shelf life of juice was established within 15 days.